Assessing Advances and Challenges in Technical Education in Brazil - Almeida, Rita; Amaral, Nicole; de Felicio, Fabiana (Washington, DC: World Bank, 2015)
As Brazil is massively investing in a scale-up of in vocational education and training (VET) through the national flagship program, PRONATEC, this report assesses institutions and policies in VET taking an in depth critical view of upcoming opportunities. It shares international best practices on selected operational issues identified as strategic bottlenecks for the delivery of technical education. The report explores multiple sources of information including a desk review of existing reports and papers, inputs/data provided by the Ministry of Education and interviews with multiple stakeholders and practitioners at the federal and state level. The report highlights the need of promoting a better alignment between the supply and demand of skills at the sub national level and of promoting better a solid monitoring and evaluation system, including the monitoring of student learning and of the trajectories into the labor market or into higher educational degrees. Issues of student career guidance and teacher quality also emerge as areas of strategic importance to the Brazilian VET system in the years ahead.